1989
DOI: 10.1002/etc.5620081002
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of nonpolar organic chemicals on low‐carbon‐content aquifer materials

Abstract: Sorption isotherms were measured by batch equilibration methods for three nonpolar organic sorbates on seven subsurface, low‐carbon sedimentary aquifer materials. Radiolabeled (14C) 1‐methylnaphthalene, o‐dichlorobenzene and naphthalene were separately equilibrated with the sorbents to determine sorption coefficients (K). Chemical and physical properties of the aquifer materials were determined. Possible relationships between sorption coefficients and organic carbon (OC) content and other sorbent properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The leaching potential of organic pollutants such as pesticides are usually assessed by the normalized distribution of the soil organic carbon partition coefficient (K oc ) (Wauchope Stauffer et al, 1989), GUS parameters (Gustafson, 1989) and laboratory column leaching (OECD, 2003;Oppel et al, 2004). K oc values of three MC variants were calculated from their K d values in the three soils, the average values for MC-RR, LR and Dha 7 LR were 224, 46.3 and 84.8 respectively (Table 3).…”
Section: Leach Behavior Of Mcs In Chinese Agriculture Soilsmentioning
confidence: 99%
“…The leaching potential of organic pollutants such as pesticides are usually assessed by the normalized distribution of the soil organic carbon partition coefficient (K oc ) (Wauchope Stauffer et al, 1989), GUS parameters (Gustafson, 1989) and laboratory column leaching (OECD, 2003;Oppel et al, 2004). K oc values of three MC variants were calculated from their K d values in the three soils, the average values for MC-RR, LR and Dha 7 LR were 224, 46.3 and 84.8 respectively (Table 3).…”
Section: Leach Behavior Of Mcs In Chinese Agriculture Soilsmentioning
confidence: 99%
“…First, the generally lower fractions of total organic carbon may result in multiple components (e.g., organic matter plus mineral fractions) contributing to the sorption uptake of hydrophobic organic compounds. For example, Stauffer et al (1989) reported that the uptake of naphthalene and 1,2-dichlorobenzene by aquifer materials with low organic-carbon contents ( f oc < 0.10%) correlated well with organic carbon, silt, cation exchange capacity, and 1:1 clay content. Second, as a result of geological maturation, chemically-reduced, physically-condensed carbonaceous material (e.g., kerogen, unburned coal, and soot) may become more prominent and thus play an even more significant role in the uptake of hydrophobic organic compounds for these low organic-carbon-content aquifer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular-scale chemical and biochemical processes at mineral–water interfaces (MWIs) play important roles in the fate and transport of contaminants in soils and sediments. For soils and sediments with low organic carbon (<0.1%), sorption of contaminants into the mineral phase is commonly assumed to be the major mechanism for contaminant retention. In particular, clay minerals, such as smectites, palygorskite, and zeolites, are critical players in the transport and fate of contaminants and have drawn significant attention as suitable materials for environmental remediation. …”
Section: Introductionmentioning
confidence: 99%